Near‐Quantitative Preparation of Short Single‐Stranded DNA Circles. Issue 16 (8th March 2023) - Paluzzi, Victoria E.; Zhang, Cuizheng; Mao, Chengde
Abstract: Small, single‐stranded DNA (ssDNA) circles have many applications, such as templating rolling circle amplification (RCA), capturing microRNAs, and scaffolding DNA nanostructures. However, it is challenging to prepare such ssDNA circles, particularly when the DNA size becomes very small (e.g. a 20 nucleotide (nt) long ssDNA circle). Often, such short ssDNA dominantly form concatemers (either linear or circular) due to intermolecular ligation, instead of forming monomeric ssDNA circles by intramolecular ligation. Herein, a simple method to overcome this problem by designing the complementary linker molecules is reported. It is demonstrated that ssDNA, as short as 16 nts, can be enzymatically ligated (by the commonly used T4 DNA ligase) into monomeric ssDNA circles at high concentration (100 μM) with high yield (97 %). This method does not require any special sequence, thus, it is expected to be generally applicable. The experimental protocol is identical to regular DNA ligation, thus, is expected to be user friendly for general chemists and biologists. Abstract : A new design of splint strands allows for the near‐quantitative monomeric cyclization of single DNA strands as short as 16 bases long by DNA T4 ligase. Circular DNA molecules have enhanced chemical stability in biological fluids, therefore, this work could facilitate a wide range of biomedical applications for single‐stranded, short nucleic acids.